A reflection on Russia’s existential nihilism from Dostoevsky’s crime and punishment and notes from the underground - Tahsin, Anika (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.